2022
DOI: 10.3390/ijerph20010196
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Workplace Violence against Healthcare Workers: A Multidisciplinary Team for Total Worker Health® Approach in a Hospital

Abstract: The risk of aggression against healthcare workers (HCWs) is a globally well-known topic. However, workplace violence (WV) is often considered as part of HCW’s job, leading to a general underreporting. This cross-sectional study aims at providing a descriptive analysis of aggressive acts against HCWs registered in a 34-month period in a pediatric hospital. According to a specific protocol, each aggressive act was analyzed by a multidisciplinary team using the “Modified Overt Aggression Scale” (MOAS), the “Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Similar studies in the literature have reported high levels of WPV among healthcare workers. 4,21 In a similar study in Turkey, it was determined that nurses working in the pediatric emergency department were exposed to WPV due to reasons such as crowded emergency departments, heavy workload, unmet expectations and concerns of parents, and intervention in medical procedures like intravenous access. 22 In a children's hospital in China, 68.6% of healthcare workers experienced at least one WPV incident involving non-physical and/or physical violence in the past year, and emergency service workers were exposed to physical violence (69.6%) more than other services.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar studies in the literature have reported high levels of WPV among healthcare workers. 4,21 In a similar study in Turkey, it was determined that nurses working in the pediatric emergency department were exposed to WPV due to reasons such as crowded emergency departments, heavy workload, unmet expectations and concerns of parents, and intervention in medical procedures like intravenous access. 22 In a children's hospital in China, 68.6% of healthcare workers experienced at least one WPV incident involving non-physical and/or physical violence in the past year, and emergency service workers were exposed to physical violence (69.6%) more than other services.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in similar studies, most of the physical and verbal abusers in pediatric healthcare workers were the caregivers/relatives of the patients. 4,5,36 Gillespie argues that all patients and their relatives should be treated as if they tend to commit violence. Employers should be aware of the impact of violence on employee and patient care and how essential it is to seek help when violence occurs and take measures to prevent violence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations